The elusive link between FDI and economic growth - Agustín Bénétrix; Hayley Pallan; Ugo Panizza (Graduate Institute of International and Development Studies, 2022)
This paper revisits the link between FDI and economic growth in emerging and developing economies. When we study the early decades of our sample, we find that there is no statistically significant correlation between FDI and growth for countries with average levels of education or financial depth. In line with previous contributions, we find that this correlation is positive and statistically significant for countries with sufficiently well-developed financial sectors or high levels of human capital. However, we also find that the link between FDI and growth varies over time. For more recent periods, we find a positive and statistically significant relationship between FDI and growth for the average country, with local conditions having a negative effect on this link. We also develop a novel instrument aimed at addressing the endogeneity of FDI inflows. Instrumental variable estimates suggest that our results are unlikely to be driven by endogeneity.
Keywords: F21; F43; C21; C26; 330; FDI; Economic Growth; Human Capital; Financial Development